An evolving ASEAN vision and reality. - Menon,Jayant ([Manila] Asian Development Bank, 2019)
The formation of ASEAN in 1967 was originally driven by political and security concerns. In the decades that followed, ASEAN scope evolved to include an ambitious and progressive economic agenda. In December 2015, the ASEAN Economic Community (AEC) was formally launched. Although AEC has enjoyed some notable successes, its vision of economic integration has yet to be fully realized. The publication reviews the evolution of ASEAN economic integration and assesses the major achievements. It also examines the challenges that have emerged during the past decade and provides recommendations on how to overcome them.
Keywords: Asia -- Economic integration; Industry and state; Electronic books